MATHEMATICAL MODEL OF DETERMINING OPTIMAL STRUCTURE OF LIVESTOCK AND ITS INCOME MAXIMIZATION - Davaajav, Altankhuyag; Rentsen, Enkhbat; Natsagdorj, Tungalag (Journal of Business and Innovation (Бизнес & Инноваци), 2025)
The livestock sector is highly dependent on natural and climatic conditions, and disasters can have consequences such as livestock population decline, reduced fertility, increased livestock diseases, and loss of herd structure. This can lead to increased poverty and unemployment in society and the economy, a decline in the standard of living of the people, and an impact on the sector’s production, creating economic instability. Therefore, by optimizating and managing of the livestock structure, it is possible to stabilize production volume and economic efficiency of the sector. In this article, a new dynamic growth model that provides the optimal structure of livestock is proposed, and the forecast of the sheep flock of Zavkhan aimag has been done until 2034. Then, the policy of maximizing the income from sheep wool was formulated as a linear programming problem. Based on statistical data, and the numerical results were performed on the “Matlab” program. The proposed approach can be used as an advanced management tool at the national, regional, aimag, soum, and household levels.